Holocentric repeat landscapes: From micro-evolutionary patterns to macro-evolutionary associations with karyotype evolution - Cornet, Camille; Mora, Pablo; Augustijnen, Hannah; Nguyen, Petr; Escudero, Marcial; Lucek, Kay (Molecular ecology, 2024)
Repetitive elements can cause large-scale chromosomal rearrangements, for example through ectopic recombination, potentially promoting reproductive isolation and speciation. Species with holocentric chromosomes, that lack a localized centromere, might be more likely to retain chromosomal rearrangements that lead to karyotype changes such as fusions and fissions. This is because chromosome segregation during cell division should be less affected than in organisms with a localized centromere. The relationships between repetitive elements and chromosomal rearrangements and how they may translate to patterns of speciation in holocentric organisms are though poorly understood. Here, we use a reference-free approach based on low-coverage short-read sequencing data to characterize the repeat landscape of two independently evolved holocentric groups: Erebia butterflies and Carex sedges. We consider both micro- and macro-evolutionary scales to investigate the repeat landscape differentiation between Erebia populations and the association between repeats and karyotype changes in a phylogenetic framework for both Erebia and Carex. At a micro-evolutionary scale, we found population differentiation in repeat landscape that increases with overall intraspecific genetic differentiation among four Erebia species. At a macro-evolutionary scale, we found indications for an association between repetitive elements and karyotype changes along both Erebia and Carex phylogenies. Altogether, our results suggest that repetitive elements are associated with the level of population differentiation and chromosomal rearrangements in holocentric clades and therefore likely play a role in adaptation and potentially species diversification.
Keywords: Lepidoptera; Genetic Speciation; speciation; Carex (rostlina); motýli; populační genetika; Butterflies; Genetics, Population; fylogeneze; Phylogeny; Repetitive Sequences, Nucleic Acid; transposable elements; karyotyp; molekulární evoluce; biologická evoluce; Evolution, Molecular; Erebia; vznik druhů (genetika); Animals; Biological Evolution; zvířata; Carex Plant; repetitivní sekvence nukleových kyselin; Carex; Karyotype